Bark to the future - Quinn, Spencer (Quinn, Spencer. Chet and Bernie mystery, 2022)
"When Chet the dog, "the most lovable narrator in all of crime fiction" (Boston Globe), and his human partner, PI Bernie Little, are approached by down-and-out older man with a cardboard sign at an exit ramp, Bernie is shocked to discover the man is a former teammate from his high school baseball team. Chet and Bernie take Rocket out for a good meal, and later, Bernie investigates Rocket's past, trying to figure out what exactly went wrong. Then, Rocket goes suspiciously missing. With his former teammate likely in danger, Bernie goes back to his old high school for answers, where much that he remembers turns out not to be true-and there are powerful and dangerous people not happy with the questions Bernie is asking. Bernie soon learns that he misunderstood much about his high school years - and now, Chet and Bernie are plunged into a dangerous case where the past isn't dead and the future could be fatal"--